Teacher Loyalty as Assessed from Emotional Intelligence, Work Environment, and Leadership Style at Ar-Risalah Islamic Elementary School, Klaten - Jamaludin Rusydi; Sudarwati; Istiatin (STIE PENA, 2026)
This study aims to analyze the influence of emotional intelligence, work environment, and leadership style on teacher loyalty at SD IT Ar-Risale Klaten. This research employs a quantitative approach with a descriptive research design. The population of this study consists of all teachers at SD IT Ar-Risale Klaten, totaling 35 teachers. The sampling technique used is saturated sampling (census), in which the entire population is used as the research sample. Data were collected through observation, documentation, questionnaires, interviews, and literature study. Data analysis was conducted using multiple linear regression, supported by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that emotional intelligence has a positive and significant effect on teacher loyalty at SD IT Ar-Risale Klaten. Meanwhile, the work environment does not have a significant effect on teacher loyalty. Leadership style also does not have a significant effect on teacher loyalty, as the significant value is at the threshold of the established confidence level. The coefficient of determination shows that emotional intelligence, work environment, and leadership style simultaneously explain 71.0% of teacher loyalty, while the remaining percentage is influenced by other factors outside the research model. Keywords: Teacher Loyalty, Emotional Intelligence, Work Environment, Leadership Style.